(3eMGhQI KjGJjJhS dCadGWhf Ch Yf GdYdes - (3eWQ, CejQI Mdejs ((3GdbGgQIs (3OGQ ZQjH ddWHGYI hGdfTQ hGdJhRjYs, 2000)
(3gPG GdcJGH JQLeI ObjbI deMGhQI KjGJjJhS hgj fU ef CcKQ fUhU GdadSaI GdbOjeI eYGUQI Gdjhe , heMGhQI KjGJjJhS ceG UhQgG CadGWhf jQhjgG EbdjOS hgh CcHQ JdGejP SbQGW heDSS GdadSaI GdejLGQjI , ceG XgQ SbQGW ajgG aj OhQ ef jeGQS egfI JhdjO GdCacGQ ajMK KjGJjJhS Ydi ENQGL eG aj HGWfg ef MbGFb(B.(3JYO eMGhQI KjGJjJhS ef CcKQ eMGhQGJ CadGWhf MjhjI hNUhHI hKQGA aj GdCacGQ , hPdc dCgejI GdehVhY GdPj JfGhdJg hgh WHjYI GdeYQaI , hef Cge eG fGbTg CadGWhf GdfXQjI GdMSjI ceG fGbT adSaI GdJZjQ hGdUjQhQI GdOGFeI GdeSJeOI ef adSaI gjQbdjWS , ceG CTGQ Edi VQhQI GaJQGV GdeKd GdYbdjI hbOe eMGhdJjf CNQjjf dJYQja GdYde(B. (3hCNP CadGWhf gfG aj GYJHGQg cKjQG ef GdbVGjG GdJj de Jcf hGVMI aj GdeMGhQGJ GdSGHbI , adbO CMGWJ eMGhQI KjGJjJhS HcKjQ ef GdbVGjG GdJj CKjQJ aj GdeMGhQGJ GdeJCNQI ShGA YfO CadGWhf Ch YfO eYGUQjgs
11
Keywords: (3GdadSaI GdjhfGfjIs